(3w-7)(5w-8)=

Simple and best practice solution for (3w-7)(5w-8)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3w-7)(5w-8)= equation:


Simplifying
(3w + -7)(5w + -8) = 0

Reorder the terms:
(-7 + 3w)(5w + -8) = 0

Reorder the terms:
(-7 + 3w)(-8 + 5w) = 0

Multiply (-7 + 3w) * (-8 + 5w)
(-7(-8 + 5w) + 3w * (-8 + 5w)) = 0
((-8 * -7 + 5w * -7) + 3w * (-8 + 5w)) = 0
((56 + -35w) + 3w * (-8 + 5w)) = 0
(56 + -35w + (-8 * 3w + 5w * 3w)) = 0
(56 + -35w + (-24w + 15w2)) = 0

Combine like terms: -35w + -24w = -59w
(56 + -59w + 15w2) = 0

Solving
56 + -59w + 15w2 = 0

Solving for variable 'w'.

Factor a trinomial.
(8 + -5w)(7 + -3w) = 0

Subproblem 1

Set the factor '(8 + -5w)' equal to zero and attempt to solve: Simplifying 8 + -5w = 0 Solving 8 + -5w = 0 Move all terms containing w to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -5w = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -5w = 0 + -8 -5w = 0 + -8 Combine like terms: 0 + -8 = -8 -5w = -8 Divide each side by '-5'. w = 1.6 Simplifying w = 1.6

Subproblem 2

Set the factor '(7 + -3w)' equal to zero and attempt to solve: Simplifying 7 + -3w = 0 Solving 7 + -3w = 0 Move all terms containing w to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -3w = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -3w = 0 + -7 -3w = 0 + -7 Combine like terms: 0 + -7 = -7 -3w = -7 Divide each side by '-3'. w = 2.333333333 Simplifying w = 2.333333333

Solution

w = {1.6, 2.333333333}

See similar equations:

| (3a-7)(5w-8)= | | 8/x=4/15 | | 9/4÷18/7 | | X*7/8 | | 0.19x+0.5(x-4)=0.01(2x-1) | | 18/x=12/28 | | 0.09Xx=105.53 | | -x^5=8 | | 4a+b=45 | | 4(5x-4)=104 | | 3a-6=-18 | | 32+x+43=180 | | 54x^2-87+35=0 | | (5-y)(3y+8)=0 | | 4a+b=27 | | 2.5x+3.75=15 | | 9ab-6a+5b-3= | | b+9+6b-9= | | 3x+11=-7+x | | 3sinx=-1.2 | | 22=7.34+b | | 2m-10+5m-80=180 | | 2(3s+6)=32 | | 4z+3-9x= | | 2k+9k= | | 8x+8=2x+3 | | y=2xy+6y-10 | | 16.95=1/x | | 5(4+2x)+2x=176 | | 3+2m-7=10 | | Y2=-1/4x | | 9x-(2x-10)=40 |

Equations solver categories